How to promote agricultural enterprises to reduce the use of pesticides and fertilizers? An evolutionary game approach - He, Qizheng; Sun, Yong; Yi, Maoan; Huang, Huimin (Frontiers in Sustainable Food Systems, 2023)
With increasing awareness of environmental protection, food safety has become an increasingly important concern for people. The excessive use of pesticides and fertilizers by agricultural enterprises poses a threat to food safety. However, effective promotion of their reduction faces many difficulties. To analyze how to promote the reduction of pesticide and fertilizer use and the path of decision-making evolution of different stakeholders under the changes of different influencing factors, this paper considers the interests of the government, agricultural enterprises and consumers, and constructs an evolutionary game model between the government and agricultural enterprises. The study found that: (1) the governance evolutionary game of reducing the use of pesticides and fertilizers can achieve four stable evolutionary strategies, among which the ideal stable state from a multi-centre governance perspective is the government choosing the regulatory strategy and agricultural enterprises choosing pesticide and fertilizer use reduction strategy. (2) The reward measures taken by the government have a more significant impact on both parties, and in the actual regulatory process, reward measures should be used cautiously, and regulatory mechanisms should be strengthened. (3) The green preferences of consumers are a key exogenous variable that significantly affects the decisions of agricultural enterprises and government. This study improves the policy analysis of pesticide and fertilizer use reduction in the Chinese context and provides innovative ideas for building a policy system to reduce the use of pesticides and fertilizers. The research conclusions provide guidance for promoting the reduction of pesticides and fertilizers use by agricultural enterprises.